Galectin-3 and Plasma Cytokines in Patients With Acute Myocardial Infarction - (:unkn) unknown (AMER SOC CLINICAL PATHOLOGY, 2014)
Objective: To investigate the concentrations of plasma cytokines and Galectin-3 (Gal-3) as inflammatory markers in patients with acute myocardial infarction (AMI). Methods: The study population consisted of 29 patients with AMI and 29 healthy control subjects. We measured Gal-3, tumor necrosis factor alpha (TNF-alpha), and interleukin-6 (IL-6) levels in plasma using enzyme-linked immunosorbent assays (ELISAs). We measured levels of C-reactive protein (CRP) via the nephelometric method. Results: Patients with AMI showed significantly higher plasma Gal-3, TNF-alpha, and IL-6 levels compared with controls. Gal-3 levels were positively and significantly correlated with plasma IL-6, TNF-alpha, and CRP levels in the control and patient groups. Conclusion: Our findings suggest that Gal-3 can be a new circulating biomarker of inflammation associated with AMI.
Keywords: Galectin-3; AMI; inflammation; cytokines; CRP; TNF-alpha; ACUTE CORONARY SYNDROME; TUMOR-NECROSIS-FACTOR; C-REACTIVE PROTEIN; ARTERY-DISEASE; HEART-FAILURE; INTERLEUKIN-6; INFLAMMATION; CELLS; RELEASE; MARKERS